No evidence for short‐term evolutionary response to a warming environment in Drosophila - Santos, Marta A. (2022)
Adaptive evolution is key in mediating responses to global warming and may sometimes be the only solution for species to survive.Such evolution will expectedly lead to changes in the populations’ thermal reaction norm and improve their ability to cope with stressful conditions. Conversely, evolutionary constraints might limit the adaptive response. Here, we test these expectations by performing a real-time evolution experiment in historically differentiated Drosophila subobscura populations. We address the phenotypic change after nine generations of evolution in a daily fluctuating environment with average constant temperature, or in a warming environment with increasing average and amplitude temperature across generations. Our results showed that (1) evolution under a global warming scenario does not lead to a noticeable change in the thermal response; (2) historical background appears to be affecting responses under the warming environment, particularly at higher temperatures; and (3) thermal reaction norms are trait dependent: although lifelong exposure to low temperature decreases fecundity and productivity but not viability,high temperature causes negative transgenerational effects on productivity and viability, even with high fecundity. These findings in such an emblematic organism for thermal adaptation studies raise concerns about the short-term effciency of adaptive responses to the current rising temperatures.